2021
DOI: 10.3390/ijms23010134
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine–Cysteine Motif Chemokine Receptor 5 Expression in Letrozole-Induced Polycystic Ovary Syndrome Mice

Abstract: Polycystic ovary syndrome (PCOS), which affects 5–10% of women of reproductive age, is associated with reproductive and metabolic disorders, such as chronic anovulation, infertility, insulin resistance, and type 2 diabetes. However, the mechanism of PCOS is still unknown. Therefore, this study used a letrozole-exposed mouse model in which mice were orally fed letrozole for 20 weeks to investigate the effects of letrozole on the severity of reproductive and metabolic consequences and the expression of cysteine–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These are in line with the study in which supplementation with TC extracts has been shown to significantly reduce the risk of morphological abnormalities in the ovaries due to radiation exposure [52]. Hypertrophy, as well as the formation of black patches and granular alterations, were observed in previous research, and these may be seen with the naked eye after DHEA treatment [50]. Treatment with metformin reduced the black spots and granulation but not as well as in TC-treated groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These are in line with the study in which supplementation with TC extracts has been shown to significantly reduce the risk of morphological abnormalities in the ovaries due to radiation exposure [52]. Hypertrophy, as well as the formation of black patches and granular alterations, were observed in previous research, and these may be seen with the naked eye after DHEA treatment [50]. Treatment with metformin reduced the black spots and granulation but not as well as in TC-treated groups.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism whereby the active components of TC increase muscle glucose absorption is supported by the Insulin Sensitivity Index QUICKI. Treatment with TC oil and HA extracts demonstrated a dose-dependent improvement in the activity of beta cells, reflected in the HOMA-Beta values [ 50 ]. These findings are consistent with earlier findings that TC reduced fructose-induced increases in blood sugar, insulin, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 CCL5 levels in the blood and visceral WAT have been shown to be elevated in letrozole-induced PCOS in mice and in PCOS patients. 43,44 Our previous study showed that T+WSD treatment or the consumption of WSD alone for 3 years was associated with elevated CRP levels in female rhesus macaques, 10 suggesting that longer treatment is necessary for inducing a systemic proinflammatory response in NHPs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with earlier findings that TC reduced fructose-induced increased blood sugar, insulin and triglycerides. 49 Recently published study on berberine alkaloid which is also an important chemical constituent discovered in the TC plant stem has been shown to significantly enhance glucose tolerance. 50 Treatment with berberine significantly reduces fasting plasma glucose, improves insulin sensitivity and decreases LDL-C in type 2 diabetic rats, demonstrating its potent antihyperglycaemic and hypolipidemic effects.…”
Section: Discussionmentioning
confidence: 99%